2019
DOI: 10.3390/cancers11070958
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid and Autotaxin-associated Effects on the Initiation and Progression of Colorectal Cancer

Abstract: The intestinal epithelium interacts dynamically with the immune system to maintain its barrier function to protect the host, while performing the physiological roles in absorption of nutrients, electrolytes, water and minerals. The importance of lysophosphatidic acid (LPA) and its receptors in the gut has been progressively appreciated. LPA signaling modulates cell proliferation, invasion, adhesion, angiogenesis, and survival that can promote cancer growth and metastasis. These effects are equally important fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 183 publications
(249 reference statements)
1
25
0
Order By: Relevance
“…18 Changes in LPL metabolism have been found to induce inflammatory responses, apoptosis, cell proliferation, disruptions in mitochondrial functions, and other cellular responses. [19][20][21][22][23] Studies conducted on changes in LPL levels' modulations post-CNS injury suggest that altered LPL production and degradation can disrupt the nervous system and result in neurologic disorders. [24][25][26] Previous studies have investigated the role of LPLs in regulating aqueous humor outflow and IOP, 27 mechanisms that are impaired in glaucoma, but there is still little knowledge about the role of LPLs in the ON.…”
mentioning
confidence: 99%
“…18 Changes in LPL metabolism have been found to induce inflammatory responses, apoptosis, cell proliferation, disruptions in mitochondrial functions, and other cellular responses. [19][20][21][22][23] Studies conducted on changes in LPL levels' modulations post-CNS injury suggest that altered LPL production and degradation can disrupt the nervous system and result in neurologic disorders. [24][25][26] Previous studies have investigated the role of LPLs in regulating aqueous humor outflow and IOP, 27 mechanisms that are impaired in glaucoma, but there is still little knowledge about the role of LPLs in the ON.…”
mentioning
confidence: 99%
“…Autotoxin is an ectonucleotide pyrophosphatase/phosphodiesterase (ENPP) family member which produces LPA. Up-regulated in most of the metastatic cancers, autotoxin was also associated with invasiveness and aggressive metastatic potential of cancers and was positively correlated to tumour angiogenesis in colorectal cancer [ 38 ]. Furthermore, evidence has identified autotoxins as secretory proteins in human melanoma cells, and the overexpression of autotoxins was co-relatable to increased motility and invasiveness [ 39 ].…”
Section: Lpa5 Is a Friend In Need Among Gpcrsmentioning
confidence: 99%
“…S1P has been implicated in both physiological and pathological neovascularization, as detailed in the next section. Numerous human gene analysis and preclinical studies have investigated the roles of LPA and LPA receptors [68,69]. These studies have shown that LPA is essential for vascularization [70].…”
Section: Sphingolipids In Ocular Neovascularizationmentioning
confidence: 99%
“…Numerous human gene analysis and preclinical studies have investigated the roles of LPA and LPA receptors [ 68 , 69 ]. These studies have shown that LPA is essential for vascularization [ 70 ].…”
Section: Glycerophospholipids In Ocular Neovascularizationmentioning
confidence: 99%